Compulsory treatment of drug users in Asia: designed to torture?. Issue 4 (21st December 2015) - Dolan, Kate; Worth, Heather; Wilson, David
Abstract : Purpose: – Injecting drug use is a global concern, with an estimated 16 million people who inject drugs (PWIDs) in over 148 countries. A number of Asian countries detain PWIDs for compulsory treatment. The paper aims to discuss this issue. Design/methodology/approach: – The authors reviewed the literature on compulsory drug treatment in seven Asian countries. Findings: – The authors identified 1, 269 closed settings which held over 600, 000 drug users in eight countries. The average detainee was aged from 20 to 30 years and was predominantly male. HIV risk behaviour continued in detention in some countries. In most countries treatment comprised physical labour, military drills. Methadone maintenance treatment and antiretroviral therapy were rarely available. No data were located to show detention in a closed setting treated drug dependency. Issues of concern were; no due legal process for the detention of drug users, lack of evidence-based drug treatment, lack of HIV prevention and treatment, abusive conditions, forced labour and exercise, arbitrary exit procedures and very high relapse rates. Research limitations/implications: – The review of compulsory treatment of drug users failed to find any evaluation of effective drug treatment for detainees. Instead serious breaches in human rights conditions were evident. Prominent international organisations have called for the compulsory treatment of drug users to cease. Practical implications: – Many countries are spending vast amounts of funding on ineffective treatments for drug users. Social implications: – Funding should be directed to community-based drug treatments that have been shown to work. Originality/value: – This is the largest review of compulsory treatment of drug users to date.